Electronic structure and luminescence assets in white-light emitting Ca2V2O7, Sr2V2O7 and Ba2V2O7 pyro-vanadates: X-ray absorption spectroscopy investigations. Issue 46 (24th July 2018) - Sharma, Aditya; Varshney, Mayora; Chae, Keun-Hwa; Won, Sung Ok
Abstract : Chemically synthesized pyro-vanadates exhibit sub-pentavalent V ions and white-light emission via charge transfer transitions of VO4 tetrahedra. Abstract : Ca2 V2 O7, Sr2 V2 O7, and Ba2 V2 O7 pyro-vanadates were synthesized using a modified chemical precipitation method and annealing. Detailed crystal structure, morphology, electronic structure and optical properties were investigated by XRD, UV-visible absorption, FTIR, Raman, FE-SEM, XANES, and photoluminescence spectroscopy. Rietveld refinement on the XRD patterns of Ca2 V2 O7, Sr2 V2 O7, and Ba2 V2 O7 has confirmed the triclinic structure (space group; P 1̄(2)) of the pyro-vanadates. The band gap energy of Ca2 V2 O7, Sr2 V2 O7, and Ba2 V2 O7 is estimated to be ∼2.67 eV, ∼2.97 eV and ∼3.09 eV, respectively. XANES spectra at the Ca L-edge, Sr K-edge and Ba L-edge have confirmed the Ca 2+, Sr 2+ and Ba 2+ ions in the Ca2 V2 O7, Sr2 V2 O7 and Ba2 V2 O7 compounds, respectively. V K-edge XANES spectra have strengthened the presence of sub-pentavalent V ions in all of the pyro-vanadates. O K-edge XANES spectra of Ca2 V2 O7, Sr2 V2 O7 and Ba2 V2 O7 have shown dominating tetrahedral symmetry of the V ions which is also corroborated with the V K-edge XANES. Broad-band emission spectra, ranging from 400 nm to 700 nm, have been observed from the charge-transfer transitions of VO4 tetrahedra. 3 T1 → 1 A1 and 3 T2 → 1 A1 transitions, from the VO4 tetrahedra, have provided two distinct emission peaks from the compounds which exhibit a red-shift with the decreasing ionic-radii of alkali-earth metal ions. The mixed compounds, with equal weight proportions, have shown remarkable emission characteristics towards the realization of rare-earth element free white-light-emitting devices.